THE IMPACTS OF CLIMATE CHANGE ON LIVESTOCK PRODUCTION AND PRODUCTIVITIES IN DEVELOPING COUNTRIES: A REVIEW - Fereja, Getachew Bekele (International Journal of Research -GRANTHAALAYAH, 2016)
It is true that most proportions of Africans livestock production and productivities are declined when the climate condition is not comfortable. Therefore this review was conducted to show the impacts of climate change on livestock production and productivities. The climate change especially global warming may highly influence production performance of farm animals throughout the world. While there has been occasional mention, in the global discussion on climate change there has generally been a dearth of attention paid to the animal production and productivities impacts of the proposed abatement options and some of the suggested livestock management approaches would have severe and wide-ranging impacts on the animal’s products. This is on the background that the impact of climate change on crops is well known, much less is known about the impact of climate change on livestock. Unfortunately, livestock production and productivities assumes an overriding emphasis as one of the core sectors to solve the current food challenges and bringing future food sustainability in developing countries. Out of all the factors influencing livestock production, climate, and location are undoubtedly the most significant. Climate change will have far-reaching consequences for animal production, especially in vulnerable parts of the world where it is vital for nutrition and livelihoods. The impact of climate change can heighten the vulnerability of livestock systems and exacerbate existing stresses upon them, such as drought. Parasites and diseases are among the most severe factors that impact livestock production and productivity. Animal diseases have great impact on food supplies, trade and commerce, and human health globally. Animal genetic diversity is critical for food security and rural development. It allows farmers to select stocks or develop new breeds in response to changing conditions.